Behavioural research in sexuality - "Ganguli, H. C." (New Delhi, 1988)
Sexual behavior constitutes an important segment of human behaviour. It is concerned with frequency, mutuality, circumstances etc. of the sex act, the various sexual outlets for different age groups, class and castes, the satisfactoriness etc. Studies on what men and women actually do in the area of sex shall increase our understanding of sex life in India, may lead to fruitful public debates on the subject and thereby improve the quality of life in India.
Keywords: Sex